Ovarian fibroma commonly misdiagnosed as uterine leiomyoma - Ibrahim A Abdelazim; Mohannad Abu-Faza; Khaled Abdelrazek; Osama O Amer; Svetlana Shikanova; Gulmira Zhurabekova (Wolters Kluwer Medknow Publications, 2020)
Ovarian fibroma usually misdiagnosed preoperatively as uterine leiomyoma. A 36-year-old woman, presented with abdominal pain and vomiting, provisionally diagnosed as complicated ovarian cyst. The transvaginal ultrasound and Doppler showed left solid adnexal mass with preserved ovarian blood flow. Magnetic resonance imaging showed a well-defined solid mass in the left side of the pelvis, measuring 8 cm × 10 cm most probably subserous uterine leiomyoma. At laparotomy, the solid ovarian mass was originating from the left ovary, and the microscopic examination confirmed the diagnosis of the ovarian fibroma. This report represents the preoperative misdiagnosis of the ovarian fibromas and the conservative ovarian surgery for the ovarian fibromas and the importance of the follow-up for future fertility and/or recurrence of the fibromas in young women.